La importancia del control de inventario para la toma de decisiones. - Espinoza Paredes, Yordy Steeven (My University, 2020)
The International Accounting Standard IAS2 Inventories are of vital importance when preparing accounting-administrative-financial information within commercial companies, which establishes the treatment of inventories since it forms a substantial part to generate income and growth economic. The Espinoza S.A ball company has focused on inventory control, which offers benefits for the entity including being competitive, improving production and storage control, providing effective and timely information for proper decision making. Currently, IAS2 establishes the requirements for the measurement, determination of the cost and its information to be disclosed within the financial statements, allowing the administration to implement an efficiently structured inventory management, trying to meet the needs of the demands and the objectives set for the correct decision making of the entity. Inventory control helps minimize the risk of losses, examine storage and verify rotation to avoid obsolete products and generate greater effectiveness when satisfying consumers, allowing credibility and confidence that would boost projected growth within goals. Of the entity.
La Norma Internacional de Contabilidad NIC 2 Inventarios son de vital importancia al momento de elaborar la información contable-administrativo-financiero dentro de las empresas comerciales, la misma que establece el tratamiento de los inventarios puesto que forma una parte sustancial para generar los ingresos y el crecimiento económico. La empresa de balones Espinoza S.A se ha centrado en el control de inventario, que ofrece beneficios para la entidad entre ellos ser competitivos, mejorar el control de producción y almacenamiento, otorgar información eficaz y oportuna para la adecuada toma de decisiones. Actualmente la NIC 2 establece los requisitos para la medición, determinación del costo y su información a revelar dentro de los estados financieros, permitiendo a la administración implementar una gestión de inventarios estructurada eficientemente, procurando cumplir las necesidades de las demandas y los objetivos planteados para la correcta toma de decisiones de la entidad. El control de inventario ayuda a minimizar el riesgo de pérdidas, examinar el almacenamiento y a verificar la rotación para evitar productos obsoletos y generar una mayor efectividad al momento de satisfacer a los consumidores, permitiendo ganar credibilidad y confianza que impulsaría al crecimiento proyectado dentro de las metas de la entidad.
Keywords: NIC 2; INVENTARIO; MEDICIÓN; CONTROL